IDENTIFICATION AND ANALYSIS OF STRUCTURAL-TECTONIC FEATURES OF GEOLOGICAL TERRAINS USING LINEAMENT ANALYSIS: EXAMPLES OF GEOMODELLING FOR CANADIAN AND UKRAINIAN SHIELDS - Poliakovska, K.; Ivanik, O.; Annesley, I.; Guest, N.; Otsuki, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Nowadays, rare earth elements (REEs), which belong to the group of rare metals, are considered worldwide to be strategic critical raw materials and are extremely important for the economic development of any country. Various methods and approaches are used for prospecting and exploration of deposits of these critical metals; among which the methods of 3D geological modeling are currently prioritized, which allow a comprehensive analysis of the structural features of potentially promising areas as well as individual deposits. One of the methods used for REE exploration is structural mapping combined with geological terrain analysis, including structural lineament analysis. The latter is considered an important geological tool for identifying the primary and secondary structural and tectonic features of our study areas of investigation. The objectives of the present research work are: 1) to identify structural lineaments within two studied areas – the Alces Lake area (Northern Saskatchewan, Canadian Shield) and the Western Azov region (Azov block of the Ukrainian Shield) using automated and manual approaches, 2) to compare the results obtained for both areas, and 3) to discuss interpretation/conclusions over the overall suitability of the method for the exploration purposes. In the current research, we conducted the extraction and geospatial analysis of linear features and their tectonic interpretation. During the modeling process, remote sensing and geostatistical methods were used to analyze topographic, geological and geophysical data. As a result, the main structural lineament trends for the two studied areas were identified and structural-tectonic criteria for the formation and localization of deposits of rare earth elements were determined/proposed.